Pengaruh Kualitas Produk, Harga Dan Citra Merk Terhadap Keputusan Pembelian Helm SNI - Ardhani Gita C, Firnanda; Nisa, Ainun; Nugroho, Jalu; Puteri K, Angelie; Sukma D, Arsyanti (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
Helmets are a mandatory safety device that must be used by every motorbike rider in Indonesia. Most students in Indonesia use motorbikes as a mode of transportation to support their mobility. So it can be concluded that students are a large group of helmet users in Indonesia. In this study we tried to find out how much influence price, product quality, brand image and the influence of SNI helmets had on the decision to purchase helmets for students in Yogyakarta. This study aims to determine: the effect of price on purchasing decisions of helmet products, the effect of product quality on consumer decisions in purchasing helmet products, the effect of brand image on consumer purchasing decisions on helmet products, and the influence of SNI helmets on consumer purchasing decisions. The population in this study is students in Yogyakarta. The data analysis technique uses multiple linear regression. The sample consisted of all students in Yogyakarta with 70 observations, which was carried out by purposive sampling. The results of the analysis show that product quality, price, and brand image are stated to have a partial positive effect on purchasing decisions for SNI helmets.